Consequences of mixing Acacia mangium and Eucalyptus grandis trees on soil exploration by fine-roots down to a depth of 17 m - Germon, Amandine [UNESP]; Guerrini, Irae Amaral [UNESP]; Bordron, Bruno; Bouillet, Jean-Pierre; Nouvellon, Yann; Moraes Goncalves, Jose Leonardo de; Jourdan, Christophe; Paula, Ranieri Ribeiro; Laclau, Jean-Paul [UNESP] (Springer, 2018)
Fine-root functioning is a major driver of plant growth and strongly influences the global carbon cycle. While fine-root over-yielding has been shown in the upper soil layers of mixed-species forests relative to monospecific stands, the consequences of tree diversity on fine-root growth in very deep soil layers is still unknown. Our study aimed to assess the consequences of mixing Acacia mangium and Eucalyptus grandis trees on soil exploration by roots down to the water table at 17 m depth in a tropical planted forest. Fine roots (diameter < 2 mm) were sampled in a randomized block design with three treatments: monospecific stands of Acacia mangium (100A), Eucalyptus grandis (100E), and mixed stands with 50% of each species (50A50E). Root ingrowth bags were installed at 4 depths (from 0.1 m to 6 m) in the three treatments within three different blocks, to study the fine-root production over 2 periods of 3 months. Down to 17 m depth, total fine-root biomass was 1127 g m(-2) in 50A50E, 780 g m(-2) in 100A and 714 g m(-2) in 100E. Specific root length and specific root area were 110-150% higher in 50A50E than in 100A for Acacia mangium trees and 34% higher in 50A50E than in 100E for Eucalyptus grandis trees. Ingrowth bags showed that the capacity of fine roots to explore soil patches did not decrease down to a depth of 6 m for the two species. Belowground interactions between Acacia mangium and Eucalyptus grandis trees greatly increased the exploration of very deep soil layers by fine roots, which is likely to enhance the uptake of soil resources. Mixing tree species might therefore increase the resilience of tropical planted forests through a better exploration of deep soils.
Keywords: Plantation; Forest; Deep root; Fine-root density; Root traits; Diversity; Over-yielding; Brazil